ALPERS-HUTTENLOCHER SYNDROME - T. T. Batysheva; V. M. Trepilets; L. Ya. Akhadova; G. S. Golosnaya (Эпилепсия и пароксизмальные состояния)
Alpers-Huttenlocher syndrome is a rare mitochondrial disease connected with mutations in the mitochondrial DNA replicase, polymerase gamma (POLG). The reduction of the activity within mitochondrial enzymes is connected with the reduction of replications level within the mitochondrial DNA. The disease manifests itself once the replications level reaches a critical point. We can also observe the debut variability and disease progression even among patients with identical genotypes and normal children onset up to the moment of clinical presentations debut. Seizures, liver degeneration and progressive development regression are the classical clinical triad of the disease. Seizures are usually resistant to treatment and have a status flow.Liver disfunction is one of the manifestations of the disease inevitable in the terminal stages. The disease in steadily progressive and leads to the patient s death within several years. Valproic acid causes toxic fatal hepatitis developing within several months and leading to the loss of the patent. Timely diagnosis of the disease, prescription of maintenance therapy and elimination of medications containing valproic acid from the seizures therapy can certainly increase patient s lifetime.place>.